Modi and his challenges - Kumar, Rajiv, 1951- (Bloomsbury, 2016)
"Taking India by storm, Prime Minister Narendra Modi has been one of the most talked about figures all around the world. His enigmatic persona and his forceful leadership have created a polarized world where some idolize him, while others question his motives and methods. In an attempt to break the myths around who Narendra Modi really is, the author attempts to take us through a journey of the leader's life, his political aspirations, his growth within the party, his remarkable stint in Gujarat and his performance over the last two years in Delhi. The author identifies the many formidable challenges Modi faces as the leader of the world's largest democracy that is in the midst of a complex transition and recommends measures that Modi must implement to deliver on his promises, thereby enabling India to realize its true potential."--Publisher's description.